Shifts in form and meaning in the translation of the subtitles of Battle Trip (배틀 트립) variety show ep 114 Trip to Bandung - Rio Abdu Rojak; Dianni Risda; Velayeti Nurfitriana Ansas (Journal of Korean Applied Linguistics, 2023)
The process of conveying meaning between two languages is called translation. This qualitative research study aims to depict changes in form and meaning during the translation of subtitles from the Korean variety show "Battle Trip (배틀 트립) episode 14," titled "Trip to Bandung," as it transitions from Korean to Indonesian. Additionally, this study delves into the underlying factors that contribute to these translation shifts. This research used a theory of translation shift and translation meaning shift. The data were collected by jotting down the phrases, clauses, or sentences in the subtitles that contained form and meaning shifts and classifying them into an analysis table, based on the type of translation shift. The results showed that from 147 units of analysis, there were 167 translation shifts. Almost all types of form shifts were found in this study. The most commonly occurring type of translation shift was category shifts, especially the structure and unit shifts. This was due to the differences in grammatical rules, sentence structure, and language units between the Korean and Indonesian languages. Meanwhile, the concept of meaning shift is categorized into two distinct groups: generic-to-specific transitions and shifts stemming from divergent cultural perspectives. The most dominant meaning shift was the generic-to-specific category because the translator used equivalents that were not too close but the meaning conveyed did not change. In addition, the difficulties in finding the close equivalents due to the differences in the cultural background were another factor in the occurrences of translation shifts.